Edukasi Sehat untuk Remaja: Meningkatkan Pemahaman Kesehatan Reproduksi di Padang - Nursal, Dien Gusta Anggraini; Marhamah, Adinda Syakila; Saputri, Ana; Fitri, Daniatul; Nathania, Amanda Jovita; Rizki, Noura (Warta Pengabdian Andalas, 2025)
Adolescence is a phase where the body undergoes changes in physical, social, psychological, and intellectual development. These changes often leave adolescents feeling confused and in need of guidance. A lack of knowledge and guidance can lead to various problems, particularly deviations in sexual behavior, which can affect reproductive health. The purpose of this counseling is to enhance the understanding of SMK SMAK Padang students regarding reproductive health, including adolescent growth and development, adolescent nutrition, adolescent psychology, sexuality, gender and domestic violence, reproductive tract infections (RTIs), HIV/AIDS, the future impacts of adolescent sexual behavior, and other youth-related issues. The methods used in this activity include counseling sessions supported by media such as PowerPoint presentations, posters, and leaflets, as well as pre-tests and post-tests consisting of 40 questions. Based on the T-test, a significant difference was found between the pre-test and post-test results. From these findings, it can be concluded that there is a significant difference in the average knowledge of participants between the pre-test and post-test, indicating that reproductive health counseling has a positive impact on adolescents.